A gas chromatography–mass spectrometry based study on serum metabolomics in rats chronically poisoned with hydrogen sulfide. (May 2015) - Deng, Mingjie; Zhang, Meiling; Huang, Xueli; Ma, Jianshe; Hu, Lufeng; Lin, Guanyang; Wang, Xianqin
Abstract: Hydrogen sulfide poisoning is a common occupational hazard, whose mortality and incidence rates are first and second, respectively, among occupational poisoning incidents in China. The main target organs of its toxicity are in the central nervous system and respiratory system. However, there are currently no specific direct tests that can be used to diagnose poisoned patients. In this study, we developed a serum metabonomic method using orthogonal partial least squares-discriminate analysis (OPLS-DA), based on gas chromatography–mass spectrometry (GC/MS) to evaluate the effect of chronic poisoning by hydrogen sulfide in rats. The OPLS-DA data demonstrated that the model group (n = 60) differed significantly from the control group (n = 30), suggesting that the metabolic profiles of the two groups are markedly different. Alterations in the levels of some metabolites such as citrate, galactose, lactate, mannose, inositol, urea, phosphate, alanine and valine were detected by OPLS-DA analysis. We observed changes in metabolic pathways including lipid metabolism, energy metabolism and amino metabolism in the model group. Our results indicate that GC/MS-based metabonomic methods may provide novel detection means for chronic hydrogen sulfide poisoning. Highlights: We developed a serum metabonomic method to evaluate the effect of chronic poisoning by H2 S in rats. We observed changes of lipid, energy and amino metabolism after the chronic H2 S poisoning. GC/MS-based metabonomic methods may provide novel detection means for chronic H2 S poisoning.